Coronary artery steal via large coronary artery to bronchial artery anastomosis successfully treated by operation. Issue 4 (October 1980) - St John Sutton, M G; Miller, G A; Kerr, I H; Traill, T A
Abstract : We report a patient with a large coronary artery to bronchial artery anastomosis causing angina by coronary steal. Angina was refractory to medical treatment, but successfully relieved by surgical ligation of the anastomosis.